2014
DOI: 10.1177/1753425914523460
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic inflammation of chronic rhinosinusitis with nasal polyps is related to OX40 ligand expression

Abstract: The aims of this study were to investigate OX40 ligand expression in sinus tissue from patients with nasal polyposis compared with patients with chronic rhinosinusitis without nasal polyps (NPs), and to determine if OX40 ligand expression is related to eosinophilic sinus infiltration. Twenty patients with chronic rhinosinusitis (11 with and nine without NPs) and seven controls were enrolled in the study. The mRNA expression of OX40 ligand and thymic stromal lymphopoietin and its receptor were analyzed. The imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Indeed, several groups reported that TSLP mRNA was significantly elevated in eosinophilic NPs in the US, Canada, China, Japan and Italy. 7,6771 Although it is notably difficult to detect TSLP protein in clinical samples by commercially available detection systems, Nagarkar et al and Allakhverdi et al found that TSLP activity was significantly elevated in NPs compared to control sinus tissue. 7,67 This indicates that TSLP protein is elevated in NPs.…”
Section: Type 2 Inflammation and Epithelial Cytokines In Eosinophilicmentioning
confidence: 99%
“…Indeed, several groups reported that TSLP mRNA was significantly elevated in eosinophilic NPs in the US, Canada, China, Japan and Italy. 7,6771 Although it is notably difficult to detect TSLP protein in clinical samples by commercially available detection systems, Nagarkar et al and Allakhverdi et al found that TSLP activity was significantly elevated in NPs compared to control sinus tissue. 7,67 This indicates that TSLP protein is elevated in NPs.…”
Section: Type 2 Inflammation and Epithelial Cytokines In Eosinophilicmentioning
confidence: 99%
“…TSLP and TSLP receptor have been found highly expressed in sinus mucosa of patients with CRSwNP [811], and a recent work by Golebski et al [22] was able to demonstrate that the TLR3 agonist and viral analog poly(I:C) were able to induce higher TSLP mRNA and protein expression in the epithelium isolated from nasal polyposis patients compared to epithelium form healthy controls, while a few and contrasting observations have been reported on the presence of IL-25 in CRS. IL-25 mRNA has been reported to be significantly elevated in ethmoid sinuses of CRSwNP compared to controls and CRSsNP by Lam et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…TSLP has been found highly expressed in sinus mucosa of patients with CRSwNP [811] and epithelial production of IL-25, IL-33, and TSLP has emerged as critical epithelial factors that can initiate and amplify airway inflammation [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…IL-1β and tumor necrosis factor (TNF)-α regulate TSLP transcript expression in an nuclear factor-kappa B (NF-κB)-dependent manner 39. Several researchers have demonstrated that TSLP mRNA is overexpressed in eosinophilic NP and associated with Th2 inflammation 404142. TSLP induces the differentiation of naïve T cells into effector Th2 cells via enhancement of OX40 ligand (OX40L)-OX40 axis on the interaction between dendritic cells and CD4 T cells 43.…”
Section: Pathogenesis and Endotypes Of Crsmentioning
confidence: 99%